The influence of environmental stress conditions on the formation of grain quality parameters of winter wheat varieties of Poltava State Agrarian University - Kryvoruchko, L.; Tyshchenko, V.; Makaova, B. (Scientific Progress & Innovations, 2022)
Grain quality parameters of winter wheat varieties largely depend on the climatic conditions of the region and the weather conditions of the year. The article presents the results of investigation on the formation of yields and grain quality parameters depending on the environmental stress conditions. According to the Canadian physiologist Hans Selye, the spring vegetation recovery time (early or late) can be described as stress, it is the plants response to strong negative environmental influences. The aim of the article is to evaluate the PSAU winter wheat varieties from the stability of grain quality parameters and yield level at different time of spring vegetation recovery, as well as to determine the relationship between spring vegetation recovery time and the main grain quality indicators. The experiment was conducted according to generally accepted classical methods, which are widely used in breeding practice in the creation and competitive testing of winter wheat varieties in 2019, 2020, 2021 years. The research was conducted in the department of primary seed production of the experimental field of PSAU. The content of protein and gluten was determined by the express method on the device "Infrascan - 105". Different time of spring vegetation recovery have been recorded: early time (2019 year), late time (2021 year), without cessation of vegetation (2020 year). According to the results of the study, it was established that in the year without cessation of vegetation the highest content of protein and gluten was observed among the studied varieties of winter wheat. The Sahaidak variety stood out - the protein content was 16.1% and gluten 31.5 %. Analysis of yield of winter wheat varieties at different times of spring vegetation recovery showed that the average yield of varieties was the highest in the studied years in 2020, when the vegetation did not stop at all, and the lowest yields of the studied varieties were observed at the late spring vegetation recovery date.